Mechanisms for ensuring property rights during the tokenization of real-world assets - Leshchenko, Yulia (Український політико-правовий дискурс, 2026)
The relevance of the study is determined by the growing adoption of real-world asset tokenization and the increasing role of digital technologies in the ownership, circulation, and management of property rights. The conversion of real estate, securities, financial claims, intellectual property, and other assets into tokenized forms creates new opportunities for enhancing liquidity, facilitating ownership fractionalization, and attracting investment. At the same time, the transformation of traditional ownership models raises important questions concerning the protection of property rights, the legal significance of tokenized representations, and the achievement of legal certainty in transactions involving digital assets. The purpose of the article is to substantiate the mechanisms for ensuring property rights during the conversion of real-world assets into tokenized forms and to determine directions for their improvement in the context of the digitalization of property relations. Methods. The study employs systemic, formal-legal, comparative-legal, and logical-analytical methods. The conceptual and legal foundations of property rights protection in the process of asset tokenization are examined. The mechanisms for recording, transferring, and exercising ownership rights within tokenized ecosystems are analyzed, together with the relationship between digital tokens and underlying assets as a prerequisite for legal certainty. It is revealed that the effective protection of property rights depends on the existence of a legally recognized connection between a tokenized representation and a real-world asset, ensuring the verification, exercise, and protection of rights regardless of their digital form. It is demonstrated that blockchain technologies and smart contracts enhance the efficiency of asset circulation but do not eliminate the need for legal mechanisms of verification, supervision, control, and enforcement. Results. It is established that the most significant risks for holders of tokenized assets are associated with the uncertain legal status of tokens, fragmented regulatory frameworks, difficulties in the cross-border protection of rights, challenges in substantiating claims to underlying assets, and the limited harmonization of dispute resolution approaches. Conclusions. The necessity of improving asset verification procedures, audit mechanisms, disclosure requirements, digital identity solutions, and the harmonization of international regulatory approaches is substantiated. It is concluded that the effectiveness of tokenization depends not only on the technological capabilities of digital platforms but primarily on the ability of legal systems to maintain a stable and legally enforceable connection between a token and its underlying asset. Future research should focus on the development of legal mechanisms for controlling digital assets, improving models for the protection of token holders, and establishing international standards for the regulation of tokenized ownership.